Adsorption Kinetics of of Protcocatechuic Acid From Aqueous solutions onto Activated Carbon Derived From Charcoal - علي علي; عوض عادل; الوعري لينا (Latakia University Journal -Engineering Sciences Series, 2020)
Commercial activated carbon derived from charcoal was used as an adsorbent to remove protcocatechuic acid from its aqueous solution. Activated carbon was crashed and separated into four granular sizes A,B,C ,and D. Five initial concentrations of protcocatechuic acid(10,20,30,40,50 ppm) were used to investigate the effect of initial concentration of pollutant on the adsorption on activated carbon. Adsorption isotherm studies indicated that activated carbon satisfy Langmuir and Freundlich models. The maximum adsorption capacity was found to be 0.36 mmol/g for granular size A. Pseudo second order fitted the adsorption. The Elovitch equation was valid for the granular size of activated carbon C,D at all initial concentrations of protcocatechuic acid as the validity standard was less than 10. The values of diffusivity constants D are different according to the granular sizes of the adsorbent (A, B, C, D) as following :D(A)>D(B)>D(C)>D(D).